Populism and social media use: comparing the Indian Prime Minister Narendra Modi's strategic use of Twitter during the 2014 and the 2019 election campaigns. Issue 2 (3rd April 2023) - Sharma, Neelam
Abstract: Populist leaders' charisma, and their ability to connect directly with the voters, usually via social media platforms, characterize the populist communication style. This study, with its focus on Indian Prime Minister Narendra Modi's 2014 and 2019 online election campaigns, extends our understanding of how populist leaders change their online communication strategy to seek votes during two different elections. After analyzing and comparing Modi's tweets from 2014 with his 2019 online campaign, this study demonstrates that Modi, as a first-time contender, employed a key populist strategy of attacking opposition and elites, along with promising economic growth, in 2014. However, as an incumbent in 2019, he primarily used Twitter for self-promotion and to establish a direct connection with voters. While his attacks on opposition reduced significantly, his engagement with the mainstream media increased in the latest elections. This paper also discusses the increasing digitalization and its impact on populist communication.